Kallmann Syndrome - causes, symptoms, treatment - review of literature - Żak, Natalia (Quality in Sport, 2024)
Background: Kallmann syndrome is a rare congenital disorder characterized by hypogonadotropic hypogonadism and anosmia or hyposmia. KS results from abnormalities in the migration of GnRH neurons from the nasal placode to the hypothalamus. The prevalence of KS is estimated to be approximately 1:30,000 in males and 1:125,000 in females. KS manifests at various stages of life, ranging from the neonatal period through adolescence to adulthood. In the neonatal period, boys may present with cryptorchidism and micropenis, while symptoms in girls may be less apparent. During adolescence, patients often experience the absence or incomplete development of secondary sexual characteristics. In adulthood, KS often leads to infertility, cardiovascular issues, and neurological symptoms. Diagnostic methods include olfactory tests and hormonal analysis, assessing levels of gonadotropins, testosterone, LH and FSH. MRI can reveal structural abnormalities in the olfactory system. Aim of study: The goal of this article was to gather information about the Kallmann syndrome, focusing on its epidemiology, etiology, characteristic features, and treatment strategies. Materials and Methods: A review of the literature available in the “PubMed”, Google Scholar and Medline databases. The search was performed by using following keywords: “kallmann syndrome”, “anosmia”, hypogonadotropic hypogonadism”. Results and conclusions: Kallmann syndrome is a complex condition that necessitates a multifaceted approach to diagnosis and treatment. Early identification of the disorder is crucial, allowing for the timely initiation of appropriate hormonal therapy and psychological support, which significantly improves the quality of life for patients. Further research into the genetic and neurobiological mechanisms of KS is essential for the development of more effective therapeutic and diagnostic methods.